Growth and pigment biosynthesis of Spirulina platensis as affected by Pb2+ concentrations - Arunakumara, KKIU; Xuecheng, Zhang; Yijing, Zhou (Bangladesh Journal of Botany, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Growth and pigment biosynthesis of Spirulina platensis Geitler, an edible cyanobacterium were stimulated at low concentration (1 mg/l) of Pb2+. The pigment biosynthesis was found to decrease with increasing Pb2+concentrations. The ratio between chlorophyll a and Î² carotene was constant regardless of the Pb2+concentration in the medium indicating that both are equally affected by Pb2+. Â  Key words: Growth, Pb2+, Pigment biosynthesis, Spirulina platensis DOI = 10.3329/bjb.v36i2.1509 Â  Bangladesh J. Bot. 36(2): 177-179, 2007 (December)